KNOWLEDGE AND ATTITUDE OF HEALTH CARE PROFESSIONALS TOWARDS PERSONS WITH DISABILITY - Iftikhar, Kamila; Alamgir, Ahmad; Maqbool, Shazia; Rehan, Waqar; Akhtar, Shajeel (Pakistan Armed Forces Medical Journal, 2019)
Objective: To assess the knowledge and attitude of health care professionals regarding persons with disabilities. Study Design: Cross sectional study. Place and Duration of Study: Children Hospital Complex Lahore, from Jun to Oct 2016. Patients and Methods: This study was designed to assess outcomes of knowledge and attitude of health care professionals regarding persons with disabilities among 85 health care professionals including doctors, nurses and allied health professionals of different hospitals of Lahore. A SAQ-K questionnaire regarding knowledge and ATDP-O for attitude was administered to all of them in a private and confidential setting. Data was entered and analyzed in SPSS version 21.0. Mean ± SD was calculated for SAQ-K, ATDP-O and analyzed using independent t-test and ANOVA. A p-value of <0.05 was taken as statistically significant. Results: Among eighty five subjects 48.2% were males, 62.4% of respondents had 1-10 years of experience, 49.4% were doctors, 32.9% were from allied medical professional. Mean score for ATDP was 62.3176 SD ± 15.61 with minimum score of 26 and maximum score of 102 (p=0.000). Mean score for SAQ-K questionnaire was 19.623 SD ± 2.56 with minimum score of 14 and maximum score of 27 (p=0.000). Conclusion: Overall knowledge and attitude of health care professionals towards persons with disabilities using ATDP-O and SAQ-K was poor.